The Power of the Camera-Presenting Politicians. A study in the rhetoric of camera techniques - Henrik Juel (Nordicum-Mediterraneum, 2019)
The aim of this paper is to contribute to a critical phenomenological and rhetorical discussion of how politicians appear to the general public in today’s visual digital media. Special attention is drawn to the often unnoticed, but appealing and persuasive potential of various forms of camera techniques such as zoom in/zoom out, point-of-view, and reaction-shots.